A Case Report of Angioplasty and Stenting Experience for Peripheral Arterial Disease of the Lower Limbs at Annapurna Neurological Institute - Pandey, Sandeep Raj; Jha, Anik; Acharya, Sudikchya; Dhakal, Sudan (Annapurna Journal of Health Sciences, 2023)
Atherosclerosis leading to stenosis or blockage in the major vessels of lower extremities causes peripheral arterial disease(PAD). PAD may be asymptomatic in early stage. But in late stage PAD present in the form of intermittent claudication (IC) or critical limb ischaemia (CLI) . The Fontaine classification is commonly used to measure the severity of disease which is staged from l-asymtomatic to lV-gangrene. PAD can be treated by medical , endovascular and surgical management The purpose of this case report is to consider the effectiveness of primary stenting as a treatment management for peripheral artery disease of the lower extremities.